GAMBARAN FAKTOR RESIKO IKTERUS NEONATORUM PADA NEONATUS DI RSUD KABUPATEN KEDIRI - Dwi Yuliawati; Ita Eko Suparni (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2017)
Infant Mortality Rate (IMR) in Indonesia is 22.23 per 1000 live births where neonatal mortality contributes 59% of infant deaths.The purpose of this research is to find a risk factors neonatal jaudience in neonates in Kediri Hospital. Design the research uses design descriptive research with a single variable the risk factors neonatal jaudience on neonates. Included in this study is a neonates with neonatal jaudience in Kediri Hospital on Januari - December 2015 about 34 respondents to technique sampling using a total of sampling. Data collection with record medical research conducted on 12-17 December 2016. Data analysis uses data analysis descriptive.The risk factors neonatal jaudience, among other : from the age of gestation, neonates preterm 19 ( 56 % ), aterm 15 (44%); the heavy born, neonates BBLR 24 ( 71 % ), normal weight 10 (29%); the sexes, neonates men 20 ( 59 % ), women 14 (41%); the complications, neonates with complications ( asphyxia / sepsis / sefalhematoma ) 24 ( 71 % ) and without complications ( asphyxia / sepsis / sefalhematoma ) 10 (29%); the breastfeeding, neonates were breastfed <8x/hari 7 (21%),neonates were breastfed ≥8x/hari 27 (79%). Neonatal jaudience most occur in neonates preterm, neonates with a weight low birth, neonates men, and neonates with complications ( asphyxia /sepsis / sefalhematoma ) and almost all occur in neonates given ASI ≥8x/day.